Афганистан: оппозиция и власть (60-70-е гг. XX в.) - Слинкин, М.Ф. (Культура народов Причерноморья, 2005)
In this book the author of the basis of a great deal of the original Afghan, foreign and home documents and materials investigates ideological and political views and stands of the Afghan antigovernment opposition forces in the 1960-1970s, deeply analyzes the emergence and influence of the left factor over social and political struggle in the country and also shows trends of the social-economic, political, ideological and cultural development in Afghanistan in the mentioned years. The great attention in the work is given to the description of the ethnic-national, religious, language and other peculiarities of the country and psychology, manners, customs and mode of life of the Afghans. By this book the author puts into scientific circulation many unknown or little known documents and materials from private and party-state archives? Afghanistan's official and underground publications and also eyewitnesses of those who actively participated in the described opposition movements. At the end of the book there are given selectic biographic sketches of some well-known Afghan statesmen, political, religious and military figures of the above named period. В данной книге на основе оригинальных афганских, зарубежных и отечественных документов и материалов исследованы идейные и политические взгляды и позиции афганской антиправительственной оппозиции в 60-70-х годах ХХ в., глубоко проанализированы возникновение и воздействие левого фактора на общественно-политическую борьбу в стране и показаны основные тенденции социально-экономического, идеологического и культурного развития Афганистана в указанный период. Большое внимание в книге уделено характеристике этнонациональных, религиозных, языковых и других особенностей страны и описанию психологии афганцев, их обычаев и традиций. В конце книги приводятся краткие биографические данные и характеристики ряда известных афганских государственных, политических, религиозных и военных деятелей рассматриваемого периода. Автор вводит в научный оборот многие ранее неизвестные документы и материалы из частных и партийно-государственных архивов, официальные и подпольные издания Афганистана, а также сведения очевидцев - непосредственных участников оппозиционных движений в этой стране. У даній книзі на основі оригінальних афганських, зарубіжних і вітчизняних документів і матеріалів досліджені ідейні і політичні погляди і позиції афганської антиурядової опозиції в 60-70-х роках ХХ в., глибоко проаналізовані виникнення і дія лівого чинника на суспільно-політичну боротьбу в країні і показані основні тенденції соціально-економічного, ідеологічного і культурного розвитку Афганістану у вказаний період. Велика увага в книзі надана характеристиці етнонаціональних, релігійних, мовних і інших особливостей країни і опису психології афганців, їх звичаїв і традицій. В кінці книги наводяться короткі біографічні дані і характеристики ряду відомих афганських державних, політичних, релігійних і військових діячів даного періоду. Автор вводить в науковий оборот багато раніше невідомих документів і матеріали з приватних і партійно-державних архівів, офіційні і підпільні видання Афганістану, а також відомості очевидців - безпосередніх учасників опозиційних рухів в цій країні.